Personality profiles of luxury escorts: Psychoclinical evidence in prostitution activity - Giulio Perrotta (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2021)
Purpose: This research addresses the issue of the personality profiles of subjects who undertake the activity of luxury prostitution, understood as one or more acts aimed at offering sexual services in return for payment. In this research, the theme is aimed at the psychopathological investigation of the personalities, according to the PICI-1(TA), of all those subjects who voluntarily and without any constriction or obligation, freely decide to undertake this activity, for personal reasons.  Methods: Clinical interview and administration of the MMPI-II, PICI-1 and PSM-1. Results: The research on a population sample of 838 persons showed that: 1) On the MMPI-II they reported pathological values on the scales of hypochondria, paranoia, depression, psychopathic deviance, hysteria, schizophrenia and hypomania; on the content scales, on the other hand, the scales of anxiety, depression, antisocial behaviour, social distress, anger, cynicism and family problems were pathological. 2) On the PICI-1, the data are even more significant. The male population sample singularly obtained at least 5 dysfunctional traits among borderline, narcissistic and sadistic personality disorders, for 92.38% (149/162); the remaining population sample, instead, singularly obtained at least 4 dysfunctional traits among bipolar, histrionic and psychopathic personality disorders. The female population sample singularly obtained at least 5 dysfunctional traits among borderline, narcissistic and masochistic personality disorders, for 94.35% (629/676); the remaining population sample, however, singularly obtained at least 4 dysfunctional traits among sadistic, bipolar and histrionic personality disorders. 3) On the PSM-1 other significant and relevant data appear, such as extremely high values in the marking relating to psychological abuse, physical abuse, unbalanced intra-parental relations and exposure to pornography in childhood and/or pre-adolescence, with a marked dysfunctionality on sexual conduct. On the basis of these data, it is reasonable to state that 93.37% of the selected sample of the population presents marked psychopathological traits that can be defined as a borderline, narcissistic and sadistic personality disorder, with traits very close to bipolar, histrionic and masochistic disorder, deserving of psychotherapeutic treatment. Conclusions: Based on the data obtained, it is reasonable to state that 93.37% of the selected sample of the population presents marked psychopathological traits that can be defined as a borderline, narcissistic and sadistic personality disorder, with traits very close to bipolar, histrionic and masochistic disorder, deserving of psychotherapeutic treatment.